Market, Market Mechanism and Price Levels in Islamic Microeconomics Perspective - yudi permana (UIN Sunan Gunung Djati Bandung, 2019)
This paper tries to discuss about Market, Market Mechanism and Price Levels in Islamic Microeconomics Perspective. In contrast to the conventional economy which frees the formation of price levels only on the market mechanism, determining the price level through market mechanisms in Islamic economics is based on the principles of justice in order to achieve mutual benefit (al-Mashlahah). Therefore, when inequality is detrimental to one party in a market, the role of the government in creating justice for both parties is a solution that is legitimate. This in microeconomic terminology is known as market intervention, which is carried out by the government as a step to stabilize the price level so that it does not harm one party in the market. Therefore, this study aimed to analyze the market and price levels in Islamic microeconomics with a philosophical approach. The methodology used in this study used qualitative research based on literature study. The result showed that there were some fundamental things that distinguished Islamic microeconomics from conventional in determining the price level in the Islamic market mechanism.